Non-platinum electrode materials for hydrogen evolution: effect of catalyst support and metallic phase - P. Paunović, D. Stoevska Gogovska, O. Popovski, I. Radev, E. Lefterova, E. Slavcheva, A. T. Dimitrov and S. Hadži Jordanov (Bulgarian Academy of Sciences, Union of Chemists in Bulgaria, 2011)
This work is concerned with the preparation and the characterization of nano-structured composite electrocatalytic material for hydrogen evolution based on Co as a hyper d-metallic phase and anatase (TiO2) as a hypo d-phase, both deposited on a carbon substrate. The main goal is to replace the Pt as an electrocatalytic material, partially or completely. Two types of support material were used: Vulcan XC-72 and multiwalled carbon nanotubes (MWCNTs). Also two non-platinum metals were used as a hyper d-metallic phase: Ni and Co. The best performances were shown by the Co electrocatalyst, deposited on activated MWCNTs. This one approaches and even slightly exceeds the catalytic activity of the traditional Pt electrocatalyst, deposited on Vulcan XC-72. To improve the disadvantages of this electrocatalyst (instability in acid media and passivation in alkaline media) a precious metal (Pt or Ru) was added into the metallic phase. Only 20 % of the precious metal in the metallic phase considerably improves the electrocatalytic activity for the hydrogen evolution. Co was shown to promote decreasing platinum particle size. From 12 nm in the catalyst with pure platinum as the metallic phase, the size of Pt particles decreases to 3-4 nm in the catalyst with mixed metallic phase (80% Co + 20% Pt).